Analisis Faktor-Faktor yang Mempengaruhi Minat Berinvestasi di Pasar Modal bagi Generasi Milenial - Pramudita, Ika Dwi; Anjani, Devi Nila (BISMA : Business and Management Journal, 2024)
The purpose of this research is to identify the factors influencing the millennial generation's interest in investing in the capital market. It employs a qualitative descriptive approach with the Systematic Literature Review (SLR) method. Articles were selected through Google Scholar search and filtered based on specific criteria, resulting in 11 qualifying articles. The findings indicate that factors influencing millennial interest in capital market investment include motivation, investment knowledge, risk appetite, return on investment, technological advancements, minimum capital, and self-efficacy. Two research methods were utilized: quantitative and mixed methods. The most researched factors were investment knowledge (11 times), motivation (10 times), risk preference (5 times), return on investment (3 times), technological advancements (2 times), and self-efficacy (1 time). The key factors significantly influencing millennial investment interest are investment knowledge and willingness to invest. Investment knowledge helps understand potential gains and risks, while motivation creates a drive to achieve financial goals. This combination motivates the younger generation to grasp the importance of investing for financial stability and long-term wealth growth.